Methane potential of fruit and vegetable waste an evaluation of the semi-continuous anaerobic mono-digestion - Edwiges, Thiago (Environmental technology, 2020)
The anaerobic digestion (AD) of a high diversity blend of fruit and vegetable waste (FVW) generated in tropical conditions as a single substrate was performed. A continuously stirred tank reactor (CSTR) operated in semi-continuous regime was used for AD. The reactor performance was monitored with gradually increasing organic loading rates (OLRs) from 0.5 up to 5.0 gVS L-1 d-1. The biochemical methane potential (BMP) of FVW determined by batch bottles was 360 LN CH4 kgVS-1, with a biodegradability of 79%. A stable pH with an adequate level of buffering capacity was observed during the entire experiment. Methane yield indicated the best performance at an OLR of 3.0 gVS L-1 d-1, with 285 LN CH4 kgVS-1 added, reaching 79% of BMP. At an OLR over 3.0 gVS L-1 d-1 accumulation of volatile fatty acids (VFA) was detected; in particular, propionic acid was monitored, and a decreased methane yield was detected. Biogas production rate was 1.55 LN L-1 d-1 and showed linear increase according to increases in the OLR